Editor’s Note - Momčilović, Ana (Medical Word, 2025)
Dear colleagues, respected readers, In front of you is the new, sixteenth issue of the magazine “Medical Word” in which we present five new scientific medical papers from five different areas of medical practice. Teamwork, versatility, quality work, and most of all, the desire to improve and play a role in the education of all personnel in the health profession enabled us to fill these pages and publish a new issue of the magazine, which, I hope, will be equally interesting for everyone to read. We tried to bring the latest knowledge about the medical problems we face in our daily practice, provide insight into modern medical attitudes and inform about recommendations and attitudes to solve them. In this issue, we are talking about the practice of pediatrics, children’s surgery, children’s dentistry, health care and nuclear medicine, so different areas of medicine that are ubiquitous in the era of modern practice. Original papers, case reports, and also review papers aim to provide assistance in work at all levels of health care, in terms of applying the most modern knowledge and approaches in treatment. Working diligently on all the texts, the authors presented the results of their work, thus enabling the exchange of information from medical practice, a better understanding of their importance and current answers. We invite new authors and reviewers to join us in creating the magazine, we thank everyone who has already contributed to the affirmation of “Medical Word”. Editor-in-Chief Prim. Ana Momčilović, MD, PhD, Professor of vocational studies Research Associate